6ER-023 The role of institutional review boards, and hospital pharmacists as members, in the informed consent process in clinical research: a retrospective observational study. (24th March 2020) - Villamañán, E; Sobrino, C; Freire, M; Inmaculada, JN; Luis, SR; Patricia, L; Lara, C; Fernández De Uzquiano, E; Herrero, A; Moreno, M
Abstract : Background and importance: It is the responsibility of institutional review boards (IRBs) and hospital pharmacists, as members of these boards, to review a research proposal and ensure that adequate informed consent procedures are implemented in an ethical way, promoting participant autonomy and protecting them from potential harm. In this context, informed consent forms (ICFs) have become increasingly complex and difficult for patients to understand. Aim and objectives: To analyse non-approval of clinical research by IRBs, related to deficiencies found in the ICFs. Secondary outcomes were type of objections in terms of readability, length, description of study purpose, design, expected benefits and foreseeable risks. Other ethical and legal aspects, such as voluntary agreement to participate, right to withdraw, biological sample management and access to personal data were also analysed. Material and methods: This was a retrospective observational study of the clinical studies evaluated by the IRB in a tertiary hospital. We evaluated the IRB resolutions of all clinical studies over 4 years, including interventional studies (clinical trials) and non-interventional research assessed by the IRB where a hospital pharmacist was a member of the board. The committee's decisions on approval were registered in the minutes of the meetings. The pharmacists reviewed the minutes, evaluating the final opinion of the committee (approval/non-approval of the study) in the first review. Results: A total of 91 sets of minutes, corresponding to the IRB meetings over 4 years, were analysed. In these meetings, 1858 clinical trials were evaluated (1057 clinical trials and 801 non-interventional studies). Of these, 1558 required informed consent for participation (83.9%, 95% CI 82.1–85.5) and 987 were not approved at first review due to deficiencies detected in the ICF (63.3%, 95% CI 60.9–65.7). The main reasons for non-approval were unreadability (11.7%), inadequate information given about access to personal data rights (9.2%), biological sample management (7.8%) and expected benefits (7.6%). Conclusion and relevance: There was a high proportion of deficiencies in the ICFs for clinical research. They were an important reason for non-approval of protocols evaluated by IRBs. Taken together, there are three fundamental weaknesses in ICFs where IRBs in hospitals play a key role: improving their readability, adapting them to regulations concerning data protection or biological sample management, and avoiding misleading information concerning enrolment. References and/or acknowledgements: No conflict of interest.